Cardiac Function Improvement and Bone Marrow Response – - Gustav Steinhoff (EBioMedicine, 2017)
Objective: The phase III clinical trial PERFECT was designed to assess clinical safety and efficacy of intramyocardial CD133+ bone marrow stem cell treatment combined with CABG for induction of cardiac repair. Design: Multicentre, double-blinded, randomised placebo controlled trial. Setting: The study was conducted across six centres in Germany October 2009 through March 2016 and stopped due slow recruitment after positive interim analysis in March 2015. Participants: Post-infarction patients with chronic ischemia and reduced LVEF (25–50%). Interventions: Eighty-two patients were randomised to two groups receiving intramyocardial application of 5 ml placebo or a suspension of 0.5–5 × 106 CD133+. Outcome: Primary endpoint was delta (∆) LVEF at 180 days (d) compared to baseline measured in MRI. Findings (prespecified): Safety (n = 77): 180 d survival was 100%, MACE n = 2, SAE n = 49, without difference between placebo and CD133+. Efficacy (n = 58): The LVEF improved from baseline LVEF 33.5% by +9.6% at 180 d, p = 0.001 (n = 58). Treatment groups were not different in ∆LVEF (ANCOVA: Placebo +8.8% vs. CD133+ +10.4%, ∆CD133+vs placebo +2.6%, p = 0.4). Findings (post hoc): Responders (R) classified by ∆LVEF ≥ 5% after 180 d were 60% of the patients (35/58) in both treatment groups. ∆LVEF in ANCOVA was +17.1% in (R) vs. non-responders (NR) (∆LVEF 0%, n = 23). NR were characterized by a preoperative response signature in peripheral blood with reduced CD133+ EPC (RvsNR: p = 0.005) and thrombocytes (p = 0.004) in contrast to increased Erythropoeitin (p = 0.02), and SH2B3 mRNA expression (p = 0.073). Actuarial computed mean survival time was 76.9 ± 3.32 months (R) vs. +72.3 ± 5.0 months (NR), HR 0.3 [Cl 0.07–1.2]; p = 0.067.Using a machine learning 20 biomarker response parameters were identified allowing preoperative discrimination with an accuracy of 80% (R) and 84% (NR) after 10-fold cross-validation. Interpretation: The PERFECT trial analysis demonstrates that the regulation of induced cardiac repair is linked to the circulating pool of CD133+ EPC and thrombocytes, associated with SH2B3 gene expression. Based on these findings, responders to cardiac functional improvement may be identified by a peripheral blood biomarker signature. TRIAL REGISTRATION: ClinicalTrials.gov NCT00950274.